Drug induced liver injury associated with TNF-α inhibitors – infliximab, adalimumab and etanercept: the role of the laboratory - Santos, Joana Sofia Ligeiro (2018)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2016